Endoscopic resection of sinonasal malignancies. Issue 4 (24th December 2019) - Abdelmeguid, Ahmed S.; Raza, Shaan M.; Su, Shirley Y.; Kupferman, Michael; Roberts, Dianna; DeMonte, Franco; Hanna, Ehab Y.
Abstract: Background: In this study, we evaluate our experience and the outcomes of patients with sinonasal cancer treated with endoscopic resection. Methods: Retrospective review of patients with sinonasal cancer who had endoscopic resection was conducted. The outcomes of interest included survival outcomes and surgical complications. Results: Overall, 239 patients were included. Median follow up time was 46.6 months. Of the 239 patients, 167 (70%) had a pure endonasal endoscopic approach, while 72 (30%) had an endoscopic‐assisted approach. Postoperative cerebrospinal fluid (CSF) leakage occurred in 14 patients (5.9%). Negative margins were achieved in 209 patients (87.4%). There was no significant difference in the margin status between the pure endoscopic and endoscopic‐assisted group ( P = .682). There was no significant difference in the survival outcomes between both the groups. Conclusion: Our data suggest that in properly selected patients, endoscopic approaches have acceptable morbidity with low complication rates and can provide an oncologically sound alterative to open approaches.